Advances in Plant Taxonomy and Systematics - Peruzzi, Lorenzo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint of the Special Issue "Advances in Plant Taxonomy and Systematics", includes an Editorial and fifteen high-quality papers published between April 2022 and April 2023 by global researchers. This collection addresses scholars and students interested in current progresses in taxonomy and systematics, which are crucial for all plant applications.